2017
DOI: 10.1186/s12884-017-1501-7
|View full text |Cite
|
Sign up to set email alerts
|

Women’s empowerment and experiences of mistreatment during childbirth in facilities in Lucknow, India: results from a cross-sectional study

Abstract: BackgroundRecent evidence has found widespread reports of women experiencing abuse, neglect, discrimination, and poor interpersonal care during childbirth around the globe. Empowerment may be a protective mechanism for women against facility mistreatment during childbirth. The majority of previous research on mistreatment during childbirth has been qualitative in nature.MethodsIn this analysis, we use quantitative data from 392 women who recently gave birth in a facility in the slums of Lucknow, India, to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 37 publications
3
59
1
Order By: Relevance
“…Similar findings have been reported by another study done in urban slums of Lucknow, India. [24] Okafor et al . have also reported that maternal characteristics such as age, parity, and educational status did not affect prevalence of DA significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported by another study done in urban slums of Lucknow, India. [24] Okafor et al . have also reported that maternal characteristics such as age, parity, and educational status did not affect prevalence of DA significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Observational data of deliveries at facilities in Uttar Pradesh confirmed women’s reports of mistreatment [ 25 ]. Other studies have documented factors associated with mistreatment, including women’s empowerment, presence of support person, and type of providers [ 24 , 26 , 27 ]. Women were more likely to experience mistreatment if they were less empowered [ 27 ], had no companions [ 26 ], and received care from nurses compared to physicians or midwives [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have documented factors associated with mistreatment, including women’s empowerment, presence of support person, and type of providers [ 24 , 26 , 27 ]. Women were more likely to experience mistreatment if they were less empowered [ 27 ], had no companions [ 26 ], and received care from nurses compared to physicians or midwives [ 24 ]. Research in Uttar Pradesh also found that women who reported mistreatment at the time of delivery were more likely to have a complicated delivery or postpartum complications [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, women's empowerment is commonly de ned and described using proxy procedures. These proxies include access/control over household income; women's involvement in household decision-making; perceptions of gender norms; and perceived equity in their power and resources [16] [24]. Prior literature has considered women's empowerment as the process through which those who have been left without the capacity to make informed life preferences obtain such capability comprising of several concepts, such as the capacity to access and make use of resources, the ability to move, agency, and autonomy [24].…”
Section: Independent Variablesmentioning
confidence: 99%